Harrison's principles of internal medicine - Harrison, Tinsley Randolph; Kasper, Dennis L (McGraw-Hill, Medical Publishing Division, 2005)
THE NEW COLOR OF MEDICINE HUNDREDS OF DIAGRAMS AND CLINICAL PHOTOS INTEGRATED INTO THE TEXT – FOR THE FIRST TIME IN FULL COLOR The Harrison\'s name is synonymous with internal medicine. HPIM continues to be the most authoritative and #1 selling medical textbook throughout the world. From its unique section on signs and symptoms through to the most comprehensive coverage of most all conditions seen by physician’s, Harrison\'s is the internal medicine reference of choice. Harrison\'s 16th Edition features new, expanded, revised and updated material on the key topics in medical practice today. From the latest research findings to up-to-the-minute advances in diagnostic and treatment methodologies, Harrison\'s puts the facts you need at your fingertips. The 16th Edition improves on a winning formula with: *State-of-the-art coverage of over 4,700 diseases and disorders—more than any other internal medicine text – in the areas of oncology and hematology; infectious diseases; cardiology; pulmonology; gastroenterology; clinical immunology; rheumatology; endocrinology; and neurology *A brand new full color format—665 full color drawings, 175 clinical and laboratory images, and hundreds of boxes, tables, and algorithms that use color to guide you to the information you need ASAP in everyday patient care *Thorough revision and updates of virtually all chapters *The addition of key new chapters – including extensive new coverage of Critical Care Medicine *145 algorithms for making accurate clinical decisions fast at the point of care *1,160 easy-access tables for immediate access to vital information and formulas *Cardinal manifestations of disease/signs and symptoms in 55 chapters (you’ll find yourself turning to this section over and over again). Here you will find all the major manifestations, such as fever, pain, aches and rash, presented in depth, with a referral that takes you to the disease section for the complete chapter. Stay a step ahead of everyday practice with the most authoritative, comprehensive, and useful guide to the entire spectrum of internal medicine.
Keywords: vnitřní lékařství; Internal Medicine